Use of nailfold video capillaroscopy in polycythemia vera - Emine Duygu Ersozlu,; Sibel Bakirci,; Cenk Sunu,; Zeynep Ertürk,; Seyyid Bilal Açıkgöz,; Ali Tamer, (Archives of Rheumatology, 2022)
Objectives: In this study, we aimed to investigate capillary vessel diameters and structural changes of capillaries by using nailfold video capillaroscopy (NVC) in patients with polycythemia vera (PV). Patients and Methods: This cross-sectional study included a total of 24 patients (19 males, 5 females; mean age: 59.8±12.9 years; range, 50.2 to 68 years) who were diagnosed with PV and 15 healthy controls (11 males, 4 females; mean age: 40.7±5.1 years; range, 36 to 44 years) between June 2016 and February 2017. Nailfold video capillaroscopy was performed by an experienced rheumatologist who was blinded to clinical data. The apical, arterial, and venous limb diameters of capillaries were measured and microvascular changes of capillaries were scored. Results: When capillaries were evaluated in terms of morphological structures, giant capillary was detected in 67% of the patients with PV and 0% in the control group (p<0.05). The arterial, venous, and apical diameters of the capillaries were significantly higher in the patients with PV compared to the control group (p<0.001). Conclusion: The presence of giant capillaries and the marked increase of arterial, venous, and apical diameters of capillaries seem to be related to PV. As it additionally plays an important role in diagnosis, prognosis, and treatment monitoring of certain diseases, capillaroscopy can be considered to be a promising microcirculation biomarker.